Biological activities of meroterpenoids isolated from different sources - Fuloria, Neeraj Kumar; Raheja, Radhika K.; Shah, Kaushal H.; Oza, Manisha J.; Kulkarni, Yogesh A.; Subramaniyan, Vetriselvan; Sekar, Mahendran; Fuloria, Shivkanya (Frontiers in Pharmacology, 2022)
Meroterpenoids are natural products synthesized by both unicellular organisms like bacteria and multicellular organisms like fungi, plants and animals including those of marine origin. Structurally, these compounds exhibit a wide diversity depending upon the origin and the biosynthetic pathway they emerge from. This diversity in structural features imparts a wide spectrum of biological activity to meroterpenoids. Based on biosynthetic pathway of origin, these compounds are either polyketide- terpenoids or non-polyketide terpenoids. The recent surge of interest in meroterpenoids has led to systematic screening of these compounds for a number of biological actions. Different meroterpenoids have been recorded for a broad range of operations, such as anti-cholinesterase, COX-2 inhibitory, anti-leishmanial, anti-diabetic, anti-oxidative, anti-inflammatory, anti-neoplastic, antibacterial, antimalarial, anti-viral, anti-obesity and insecticidal activity. Meroterpenoids also possess inhibitory activity against expression of nitric oxide, TNF- α and other inflammatory mediators. These compounds also show renal protective, cardioprotective and neuro-protective activities. The present review includes literature from 1999 till date and discusses 590 biologically active meroterpenoids of which 231 are from fungal sources, 212 are from various species of plants and 147 are from marine sources like algae and sponges.